Exploring the Misalignment between Business and Information Technology on the Implementation of Balanced Scorecard: Case Study of State-Owned Telecommunication Companies in Indonesia - Hardy Sundoro; Harimukti Wandebori (Faculty of Computer Science Universitas Indonesia, 2021)
Many organisations around the world have faced misalignment in attaining the alignment between business and IT. The positive effect of alignment on overall company success has been focused on previous research. On the other hand, the misalignment in the implementation of a balanced scorecard was primarily unexplored. This study aimed at identifying and evaluating the factors that contribute to a misalignment of businesses and IT. The case study methodology is conducted in two state-owned telecommunication companies in Indonesia. The telecommunication industry’s selection as the case study is because of their nature closely related to technology development and implementation. Five semi-structured interviews, field notes and business records are used to produce the data, which have been thematically analysed and further follow by cross-case analysis to compare the thematic analysis result from each company. This study has resulted in 12 factors of misalignment between business and IT that can inhibit achieving alignment in implementing a balanced scorecard. The main findings showed that human factors, enterprise architecture, and IT project implementation factors could be three main source themes that can potentially contribute to misalignment. The findings may allow researchers to devise frameworks for how misalignments can be minimised to align business and IT better. This finding also useful in practice for companies that are seeking to achieve business-IT alignment by focusing on human factors, enterprise architecture factors, and IT project implementation factors.